Are dynamic or fixed FDG‐PET measures of disease of greater prognostic value in patients with relapsed/refractory diffuse large B‐cell lymphoma undergoing autologous haematopoietic stem cell transplantation?. (4th April 2023) - Campbell, Belinda A.; Brown, Rachel; Lambertini, Alessandro; Hofman, Michael S.; Bressel, Mathias; Seymour, John F.; Wirth, Andrew; MacManus, Michael; Dickinson, Michael
Summary: Positron emission tomography (PET) response assessment using the Deauville score has prognostic utility in relapsed/refractory (R/R) diffuse large B‐cell lymphoma (DLBCL) undergoing autologous stem‐cell transplantation (ASCT). Improved predictive methods are required to identify patients with poor outcomes who may be better considered for other salvage options. We investigated the prognostic value of mean tumour volume (MTV) and maximum standardised uptake value (SUVmax) at pre‐salvage and pre‐ASCT time‐points, and the quantitative changes between scans (∆MTV and ∆SUVmax). One hundred and twenty‐five patients with R/R DLBCL underwent salvage immunochemotherapy and ASCT: 80 patients had pre‐salvage PET and 90 had pre‐ASCT PET available. With a median follow‐up of 5.6 years, 5‐year progression‐free survival (PFS) and overall survival (OS) were 52% and 65%, respectively. For patients with PET‐positive residual disease after salvage therapy, pre‐ASCT MTV was a significant negative prognosticator for PFS (HR 1.19 per 100 ml, p < 0.001) and OS (HR 1.78 per 100 ml, p < 0.001). Similarly, pre‐ASCT SUVmax was negatively associated with PFS (HR 1.08, p < 0.001) and OS (HR 1.08, p < 0.001). Notably, pre‐salvage MTV and SUVmax and ∆MTV and ∆SUVmax were not associated with PFS or OS. In conclusion, pre‐ASCT MTV and SUVmax appear to be of greater predictive value than the degree of response. Potential application may exist for PET‐directed management of R/R DLBCL patients.